(untitled) (Journal of Philosophy Culture and Political Science, 2019)
This article is devoted to a religion role in the conditions of modernization of the Kazakhstan society. Prompt process of modernization of the Kazakhstan society at a turn of the XX-XXI centuries brought to peculiar to «the religious Renaissance». At the same time, this process of spiritual revival revealed also certain problems which Kazakhstan didn’t face. Paramount task today is systematic and profound studying, monitoring of a religious situation in our country, the analysis of a condition and dynamics, religious associations. Keywords: modernization of Kazakhstan society, religious Renaissance, spiritual revival, the religious situation.